Association between aromatic amines and serum neurofilament light chain as a biomarker of neural damage: a cross-sectional study from NHANES - Lin, Tong; Mao, Haiyan; Huang, Shanshan; Chen, Jialu (Frontiers in Public Health, 2024)
Background Aromatic amines (AAs) are a group of compounds widely found in chemical industry, tobacco smoke, and during food processing, with established carcinogenic properties. To date, there have been no reports on the potential neurotoxic effects of adult exposure to AAs. Serum neurofilament light chain (sNfL) is a protein released into the bloodstream following nerve axon injury and has been validated as a reliable biomarker for various neurological diseases. However, there has been no research to investigate the relationship between AAs exposure and sNfL.Methods In this study, we selected adults (aged ≥20 years) with data on both AAs and sNfL from the National Health and Nutrition Examination Survey (NHANES) conducted in 2013-2014. We used multivariable linear regression models to explore the correlation between urinary AAs and sNfL.In total, 510 adult participants with an average age of 43.58 ± 14.74 years were included in the study. Our findings indicate that, based on univariate linear regression and between-group comparative analyses, 1-Aminonaphthalene (1-AN), 2-Aminonaphthalene (2-AN), 4-Aminobiphenyl (4-AN) and o-Anisidine (o-ANI) showed a positive correlation with serum neurofilament light chain (P＜0.05). However, multiple linear regression analysis revealed that only 2-AN exhibited a positive correlation with serum neurofilament light chain (P＜0.05), while the correlations of other compounds with serum neurofilament light chain became non-significant.Although our cross-sectional study fails to establish causal relationships or determine clinical significance, the findings indicate a potential association between adult exposure to AAs, notably 2-AN, and nerve damage. Consequently, further research is needed to explore the connection between AAs exposure, sNfL, and neurological conditions in adults.